2012
DOI: 10.3892/ijmm.2012.926
|View full text |Cite
|
Sign up to set email alerts
|

The role of diet in the pathogenesis and management of irritable bowel syndrome (Review)

Abstract: Abstract. Most patients with irritable bowel syndrome (IBS) believe that diet plays a significant role in inducing IBS symptoms and desire to know what foods to avoid. It has been found that the intake of calories, carbohydrates, proteins and fat by IBS patients does not differ from that of the background population. IBS patients were found to avoid certain food items that are rich in fermentable oligo-, di-and monosacharides and polyols (FODMAPs), but they did have a high consumption of many other FODMAP-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 102 publications
3
65
0
1
Order By: Relevance
“…The most commonly reported triggers are carbohydrates and fatty foods, milk and dairy products, wheat products, caffeine, hot spices, certain meats, cabbage, onions, peas, beans and fried and smoked foods (16)(17)(18)(19). Despite these reported effects, numerous studies have demonstrated that dietary composition does not markedly differ between patients with IBS and controls (15)(16)(17)(18)(19)(20)(21), although patients with IBS appear to have a low intake of calcium, potassium, magnesium, vitamin A, vitamin B 12 In a previous study by our group, dietary guidance administered individually to patients with IBS reduced the symptoms of the condition and improved their quality of life, in addition to affecting their habitual diet so that their intake of minerals and vitamins became normalized (18). However, two groups of patients with IBS were compared in the study; one group received individual dietary guidance, whilst the second did not receive any dietary guidance.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly reported triggers are carbohydrates and fatty foods, milk and dairy products, wheat products, caffeine, hot spices, certain meats, cabbage, onions, peas, beans and fried and smoked foods (16)(17)(18)(19). Despite these reported effects, numerous studies have demonstrated that dietary composition does not markedly differ between patients with IBS and controls (15)(16)(17)(18)(19)(20)(21), although patients with IBS appear to have a low intake of calcium, potassium, magnesium, vitamin A, vitamin B 12 In a previous study by our group, dietary guidance administered individually to patients with IBS reduced the symptoms of the condition and improved their quality of life, in addition to affecting their habitual diet so that their intake of minerals and vitamins became normalized (18). However, two groups of patients with IBS were compared in the study; one group received individual dietary guidance, whilst the second did not receive any dietary guidance.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 There are at least 10 types of endocrine cell, and they regulate gastrointestinal motility, secretion, absorption, visceral sensitivity, local immune defense, cell proliferation, and appetite. [2][3][4] Abnormal densities of gastrointestinal endocrine cells have been reported in patients with IBS, which may explain the dysmotility, visceral hypersensitivity, and abnormal intestinal secretion seen in these patients. 5 But other factors such as diet, intestinal microbiota, genetics, and low-grade infl ammation …”
Section: ■ the Mechanisms Are Complicatedmentioning
confidence: 99%
“…7 Nonceliac gluten sensitivity is often perceivable by patients, resulting in self-diagnosis and self-treatment. 4 However, it is not clear whether it is gluten or the fructans and galactans in wheat that are responsible for triggering their symptoms. 7 …”
Section: ■ Gluten Is Implicatedmentioning
confidence: 99%
“…24 İBS'de besin allerjisi varlığı ve İBS semptomlarında besin intoleransının da rol oynayacağına dair kesin bir kanıt mevcut değildir. 25 Bunlara ek olarak, son dönemde düşük FODMAP içerikli diyetin İBS semptomlarının iyileşmesinde olumlu etkilerinin olduğunu gösteren çalışmalar mevcuttur. [26][27][28] DÜŞÜK FODMAP İÇERİKLİ DİYET Düşük FODMAP içerikli diyet, fermente oligosakkaritler, disakkaritler, monosakkaritler ve polyollerin diyette azaltılması prensibine dayanmaktadır.…”
Section: İrri̇tabl Barsak Sendromu Ve Di̇yet İli̇şki̇si̇unclassified